Communication and Symbolic Capitalism. Rethinking Marxist Communication Theory in the Light of the Information Society - George Pleios (tripleC: Communication, Capitalism & Critique, 2012)
Communication is examined in the realm of Marxist theory not as an autonomous social field, but as a component in the total social structure. It is argued that there was a shift from the initial Marxist idea of forms of communication as relations of production to communication as part of the superstructure, and that this view has prevailed in Marxist theory for a long period of time. In the work of later Marxists, we can spot a re-connection of communication with the capitalist mode of production, but not with the process of structuration and changing of relations of  production. In my view, first we must connect these modifications in Marxist theory with the changes in the capitalist mode of production itself and secondly we must seek the role of communication primarily in the production process.  We stress that at the end of the 19th century there was a shift from extensive to intensive forms of surplus value which was tightly interconnected with the mass (enlarged) consumption of symbolic commodities and commodities – symbols as stimulus for the intensive production. In this way capitalism was transformed to symbolic capitalism. In the ‘60s, the symbolic logic of enlarged consumption led to the need for diverse and flexible production and therefore to the deep information – symbolic changes in technology and social organization of the labour. Thus the logic of consumption became logic of production. This made possible on one hand the shrinkage of the enlarged consumption and on the other the high productivity of the economic systems. This was the rise of a new, deep symbolic capitalism, which made possible the social change without seizing the power. Therefore, the recent developments in the capitalist mode of production takes us back to the primary Marxist notion of communication forms as relations of production and make possible to change the laters by changing the first.